Effects of tirzepatide, a novel dual GIP and GLP-1 receptor agonist, on lipid profiling in patients with type 2 diabetes. (25th November 2020) - Ruotolo, G; Roth, K.D; Milligan, P.L; Lin, Y; Wilson, J.M; Pirro, V; Duffin, K.L; Haupt, A
Abstract: Background/Introduction: In a Phase 2 trial, tirzepatide (TZP) dose-dependently reduced HbA1c, body weight and serum triglycerides in moderately obese type 2 diabetes (T2D) patients. Purpose: To understand changes in fasting serum lipids with TZP, lipidomics profiling of multiple lipid classes was conducted. Methods: Patients (n=314) were randomized to receive weekly subcutaneous TZP, dulaglutide, or placebo for 26 weeks. Shotgun lipidomic analysis was performed in positive electrospray using a Sciex Triple TOF 5600 mass spectrometer operating in MS/MSALL mode and sphingomyelin (SPM) data were acquired in positive electrospray TOF mode. Data were assessed using MMRM. Results: At 26 weeks, total cholesterol esters (CE), phosphatidylcholines (PC) and phosphatidylinositols (PI) increased with placebo; dulaglutide treatment did not affect any lipid class (Table). With TZP 10 and 15 mg, total triacylglycerides (TAG), diacylglycerides (DAG), phosphatidylethanolamines (PE), PC and PI dose-dependently decreased at 4, 12 and 26 weeks, whereas total CE and phosphatidylserines (PS) levels did not change at any timepoint. At 26 weeks, individual, but not total, SPM and ceramide (Cer) changes were observed with TZP 15 mg. Most saturated, long chain SPM (14:0, 20:0, 21:0, 22:0, 23:0, 24:0) and Cer (22:0, 23:0, 24:0) were reduced by 8–16% and 14–20%, respectively. Conversely, unsaturated SPM (24:1, 24:2) increased by 6.5% and 11.4%, and unsaturated glycosylated Cer 16:0 lactosyl and 24:1 hexosyl increased by 22.4% and 19.3%, respectively. TZP 10 and 15 mg decreased total SPM by 4–6% at 4 weeks, and total Cer between 8% and 13% at 4 and 12 weeks. Conclusions: Tirzepatide dose-dependently reduced levels of total TAG, DAG, PE, PC, and PI at all timepoints, whereas levels of saturated long chain SPM and Cer were reduced and those of some unsaturated SPM and glycosylated Cer increased at 26 weeks. Net improvements in lipidomics profiling with tirzepatide warrant further evaluation of potential benefits on cardiovascular events and NASH. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Eli Lilly and Company